Succession of embryonic and the intestinal bacterial communities of Atlantic salmon (Salmo salar) reveals stage‐specific microbial signatures - Jep, Lokesh; Kiron, Viswanath; Sipkema, Detmer; Fernandes, Jorge Manuel de Oliveira; Moum, Truls Borg (MicrobiologyOpen, 2018)
publishedVersion